Formation of lease institute as a legal category - Рибачок, Вікторія Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article examines the history of formation of lease institute as a legal category that dates from Phoenicia, Egypt, Greece and Ancient Rome and has undergone considerable development in the nineteenth century. The author agrees that despite the fact that the history of the lease agreement closely correlates to the proprietary lease, the lease agreement has its separate distinctive features inherent only to lease relations and aimed at their settlement.